ECO-FRIENDLY TRANSPORTATION: SOLAR CAR DESIGN FOR COMPETITION- PART III, ELECTRICAL SYSTEMS - Behzad Hamedi; Jack Michaud; Anthony Etzler; Danny Stover; Kyle Shah; Joey Dias; Adeel Aziz; Saied Taheri (International Journal of Innovations in Engineering Research and Technology, 2023)
This paper is the third part of a series focusing on the design and analysis of a solar car for competition. Specifically, it explores the electrical systems involved in the solar car design, including both high voltage (HV) systems like the Solar Array, Battery, and Motor, and low voltage systems such as the horn, display, driver interface systems, and the Controller Area Network (CAN bus). The study aims to develop a comprehensive understanding of the electrical architecture of solar cars, encompassing integration and communication between various components through the CAN bus. By examining the design, integration, and performance of these systems, this paper contributes to the advancement of eco-friendly transportation solutions and highlights the potential for renewable energy sources in the automotive industry. The project is undertaken by the Virginia Tech Solar Car team, as part of their participation in the solar car competition, demonstrating their expertise in sustainable vehicle design and innovation. In addition, the subsequent paper in this series (Part IV) will address the testing and validation phase of the solar car project. This paper will provide valuable insights into the practical verification of the solar car, detailing the implementation of the corresponding validation plan. By conducting rigorous testing and evaluation on physical prototypes, the performance and functionality of the solar car will be thoroughly assessed, ensuring its reliability and adherence to design specifications.